The Use of Homeopathic Medicines for the Treatment of Mastalgia and Mastopathy - Jumaeva D.R (American Journal of Bioscience and Clinical Integrity, 2025)
The Mastalgia and fibrocystic mastopathy (FCM) are prevalent benign breast disorders among women of reproductive age, often leading to physical discomfort and psychological distress. Despite a high incidence, standardized treatment protocols remain elusive. This study addresses the therapeutic gap by exploring the efficacy of homeopathic remedies, particularly Mastopol, in managing mastalgia and FCM. A clinical investigation was conducted on 40 women (average age 39.1 years) experiencing symptoms of mastopathy. Over an 8-week course, participants received Mastopol sublingually three times daily. The treatment led to significant clinical improvement: 50% of the women experienced complete relief from breast pain, while the remaining reported reduced symptom intensity. Ultrasound findings confirmed a decrease in the size and density of cystic formations in half of the cases. No adverse events were recorded, and patient satisfaction was high, with 90% rating the outcomes as "good" or "very good." The findings support the use of homeopathic treatment as a safe and effective non-hormonal alternative for managing benign breast conditions. These results underscore the therapeutic potential of Mastopol and similar remedies, emphasizing the importance of individualized, low-risk approaches to women's health. Further research in broader populations is recommended to validate these outcomes. According to the WHO definition (1984), mastopathy is a fibrocystic disease characterized by a violation of the ratio of epithelial and connective tissue components, a wide range of proliferative and regressive changes in the tissues of the mammary gland. Along with the term "mastopathy", the terms "diffuse fibrocystic mastopathy", "diffuse cystic mastopathy", "mammary gland dysplasia" are used to designate this pathological condition.